(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The purpose of this project is to design and construct automatic missile detection and destroying system. This system is designed to detect the target (missile) moving in multiple directions. The target destroying system moves automatically in the direction of missile and fires it upon fixing the target. This system consists of an intelligent sonar-based object tracking system that continuously monitors the target. Upon detecting the target, it sends the target’s location to a Central Control System. The Central Control System takes the action of moving the firing mechanism in the direction of target (missile). Upon fixing the direction, it sends the control command to firing system for attacking the target. In this project we are making use of ultrasonic radar system and a DC geared motor driven firing unit interfaced with a Microcontroller based control unit. The ultrasonic sensor movement is maintained by the servo motor fixed within it. The servo motor is made to revolve through fixed angles; if object is detected then the angle position is sent as the input to the launcher fixed servo motor. The launcher will release the missile fixed within it because the Ultrasonic sensors covers larger sensing distance, and it can detect the target in all the lighting conditions (day or night). The programming of Microcontroller is done using Embedded ‘C’.